Applying value stream mapping for productivity improvement of a metal stamping industry - Karim, A.N. Mustafizul; Jaafar, Abdul Azim; Abdullah, Muhammad Abdullah; Haque, Mahbubul; Ali, Mohammad Yeakub; Amri, Siti Amy Azline (Trans Tech Publications, Switzerland, 2012)
To sustain in business by meeting the customer expectations with limited resources under tight schedule is a great challenge for high volume manufacturing industry. In this respect Value Stream Mapping (VSM) plays an important role as a strategic tool in streamlining the processing operations and enhances capacity utilization. This study has been conducted on application of VSM in a make-to-order metal stamping company engaged in production of different stamped parts of which the LCD TV frame is a significant one. Based on the product flow analysis, a current state VSM has been constructed using pertinent data collected from the production floor. Analysis of recorded videos and time studies were performed in order to figure out the scope of improvements in framing the future state map (FSM) in the context of cycle time reduction and line balancing efficiency. As observed from the FSM, the efficiency of production line is possible to be significantly increased from about 48% to more than 93% vis-à-vis a reduced batch completion cycle time. Thus it is obvious that with minor adjustments in the system in line with the findings of the study, the industry can make a substantial improvement in their operational efficiency.